Bread Making Innovation Training And Product Innovation In Improving Community Independence Abilities - Gunawan, Agung Arif; Rini, Rosie Oktavia Puspita; Afriani, Miratia; Syaiful, Hendra (JURNAL KEKER WISATA, 2025)
This community service activity aims to provide education and knowledge about bread-making innovations to inmates, namely at the Class IIA Batam Penitentiary (Lapas) which is currently running an independence development program by establishing a bread-making business. The bread-making business is called Ropastam. This bread-making kitchen is managed by the Batam Penitentiary Work Activities Section by involving inmates who have experience in the culinary field. This bread-making activity is a positive activity for inmates, so that they do not get stressed while serving their sentence, and also for their self-development so that when they get out, they gain knowledge that they can use to open a business outside. The focus on bread-making innovations at this time is more on the product variants made or produced and the model/shape of the bread product. With the addition of types of bread fillings or shapes of bread, it is hoped that it can provide a variety of choices for consumers in buying bread products. In addition, it is also to increase the entrepreneurial spirit of bread makers. Entrepreneurship is considered one of the important keys to improving the economic welfare of the community. Through this activity, it is hoped that they can gain a better understanding of bread making techniques, variations in bread shapes and fillings and encourage them to develop creative and innovative ideas in running other businesses in the future